Indonesian Women Perspective: The Exploration of Factors Influencing the Adoption of Menstrual Cup - Oktavian Kamira; Nosica Rizkalla (Journal of Business and Management Review, 2023)
Menstruation is a natural phenomenon in women who have gone through puberty. During this period, it is very important to maintain the hygiene of the private part. Unfortunately, education about menstruation in Indonesia is still low. This lack of education about menstruation also causes the Indonesian women to be uninformed about the menstrual product other than disposable menstrual pad. Menstrual pad is considered to bring a lot of disadvantages, not only to the health but also to environment. One of the product alternatives that can be used during menstruation is menstrual cup. However, the adoption of menstrual cup in Indonesia is still very low. This study intends to explore what factors can influence the purchase intention for menstrual cup by examining consumer doubt, scepticism, familiarity, information seeking and value for money. 160 responses were collected through the survey using a self-administered questionnaire. Research hypotheses were tested using multiple regression, with SPSS software. The result of this study showed that consumer doubt, familiarity, information seeking and value for money were significant in influencing purchase intention, while scepticism was not significant. The result of this study gives insight for the companies producing menstrual cup in designing the proper strategy in promoting their products. Limitations and suggestions for further research was also discussed